THE SIGNIFICANCE OF SOCIAL MEDIA COMMUNICATION STRATEGY IN ENHANCING BRAND AWARENESS: A PHENOMENOLOGICAL STUDY ON THE FOUNDER’S EXPERIENCE OF TILOVAVE.ID - Seilla Indie Natasya; Anita Sumelvia Dewi (SOSIOEDUKASI, 2026)
The rise of social media has transformed marketing communication, particularly for MSMEs and local brands building brand awareness. It now serves not only as a promotional tool, but also as an interactive space for storytelling and creating emotional connections. This study aims to explore the meaning of social media communication strategies for increasing brand awareness, based on the subjective experience of Tilovave.id’s founder. Using a qualitative phenomenological approach, it examines the founder’s experiences, values, and meaning-making around implemented strategies. Data were collected through an in-depth interview with the founder, digital observation of social media activity, and documentation of posts and audience interactions. Thematic analysis followed stages of data condensation, presentation, and conclusion drawing. Findings reveal that Tilovave.id’s strategy is understood as building an authentic brand identity through visual consistency, experience-based storytelling, communicating quality and trust, and sustained two-way interaction. Authenticity and emotional engagement emerge as key to organic brand awareness where the audience not only recognizes the brand visually, but also develops trust and emotional bonds. The study contributes theoretically by enriching digital marketing communication research through a phenomenological lens, and practically by aiding MSMEs in designing more meaningful, authentic, and relationship-oriented social media strategies.